Primary health care management in oral health in Fortaleza, Ceará, between 1999 and 2006 - Lessa, Caroline Ferreira Martins; Vettore, Mario Vianna (Saúde e Sociedade, 2010)
This study assessed the degree of adequacy of Primary Care management in oral health in the city of Fortaleza, state of Ceará, Brazil, between 1999 and 2006. The employed methodology was based on a matrix of analysis including five dimensions: Planning and Programming, Management Support to Primary Care Professionals and Practices, Dental Assistance Offered, Health Services Utilization and Integrality of Care. The information was obtained from municipal health plans, management reports and analysis of secondary data from Sistema de Informação Ambulatorial (SIA-SUS - Outpatient Clinic Information System of Brazil's National Health System) and from IBGE (Brazilian Institute of Geography and Statistics). In addition, health indicators from the Primary Health Pact (2006) and information from oral health managers were analyzed. An improvement was observed in the first four dimensions of the matrix of analysis and only the dimension related to health services utilization declined during the period of the study. The trend of the oral health indicators was heterogeneous. While the oral health indicator "Coverage of the First Dental Consultation" decreased, the "Proportion of Specialized Dental Procedures in Relation to Individual Actions in Primary Care" showed a slight increase. It was concluded that the Primary Care management in oral health in the city of Fortaleza became adequate to the health surveillance model between 1999 and 2006. However, the decline in dental health services utilization, associated with the stability of the indicators of dental coverage and assistance, suggest the need to systematize the activities of planning and assessment of oral health actions in Primary Care in Fortaleza.